WALI NIKAH DALAM PEMIKIRAN FUQAHA DAN MUHADDITSIN KONTEMPORER - Ahmad, La Ode Ismail (LPPM IAIN Parepare, 2015)
This article deals with wali nikah (relative legally responsible for a bride) as a requirement in a wedding process. Majority of Islamic scholars (fuqaha), and also Indonesian Islamic law, always refers to male relative when they talk about wali nikah. On the other hand, contemporary Islamic scholars even give a bride a freedom to get married without a wali nikah. While the first opinion may lead to gender inequality and injustice, the latter opinion is very dangerous. From historical approach, the opinion that wali nikah always refers to male relative can be traced from Islamic legislation prescribed in the Qur?an and hadits. Referring to some contemporary Islamic scholars and muhadditsin, the writer contends that wali nikah is not an obligatory rule (rukun) of a marriage, but only serves as a monitoring apparatus. Suppose wali nikah must exist, it does not necessarily come from a bride side, but may come from a bridegroom side. Moreover, the order of wali nikah may differ from what is compiled in Islamic legal thought (fiqh).